Optimalisasi Aktivitas Mengajar Guru Melalui Inovasi Media Pembelajaran: Studi Literatur Terintegrasi - Bt samsuddin, Yati (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Improving the quality of the learning process requires teachers to adapt to technological developments and innovations in learning media. Optimal teacher teaching activities demand media that not only facilitate the delivery of material but also actively engage students. This study aims to analyze the contribution of innovative learning media to optimizing teacher teaching activities through an integrated literature review of ten nationally accredited Sinta articles and ten reputable international publications published within the last eight years. The analysis was conducted qualitatively by comparing similarities, differences, and research gaps among relevant sources. The findings reveal that interactive media, culturally-based media, and advanced technologies such as artificial intelligence positively influence teaching effectiveness and student engagement. A notable difference lies in the level of technology adoption, with international studies integrating more advanced technologies, while national studies focus on adapting to local resources. These findings highlight the need for continuous teacher training, adequate infrastructure support, and education policies that promote innovation. Further research is recommended to integrate advanced technology with local wisdom to produce effective, relevant, and sustainable learning media.